2005
DOI: 10.1016/j.femsyr.2005.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of genes in : Cloning of the maltose permease gene and expression from the divergent intergenic region between the maltose permease and maltase genes

Abstract: Hansenula polymorpha uses maltase to grow on maltose and sucrose. Inspection of genomic clones of H. polymorpha showed that the maltase gene HPMAL1 is clustered with genes corresponding to Saccharomyces cerevisiae maltose permeases and MAL activator genes orthologues. We sequenced the H. polymorpha maltose permease gene HPMAL2 of the cluster. The protein (582 amino acids) deduced from the HPMAL2 gene is predicted to have eleven transmembrane domains and shows 39-57% identity with yeast maltose permeases. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 37 publications
1
30
0
1
Order By: Relevance
“…The Srt1 protein has 12 predicted transmembrane domains (TMDs [18]) and a large extracellular loop between TMD1 and TMD2 (Figure 1C), a typical structural feature of previously characterized fungal and plant hexose transporters [8],[19]. Sequence comparisons revealed a moderate similarity (less than 30% identity) of Srt1 to a large group of transport proteins (Figure S3) that includes numerous well-characterized high-affinity monosaccharide transporters from plants and fungi as well as some low-affinity maltose transporters from Saccharomyces cerevisiae [20][22], Pichia angusta (synonym: Hansenula polymorpha [23]), or Schizosaccharomyces pombe [24]. Phylogenetic analyses revealed that Srt1 is most closely related to a small group of so-far uncharacterized proteins (Figure S3).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The Srt1 protein has 12 predicted transmembrane domains (TMDs [18]) and a large extracellular loop between TMD1 and TMD2 (Figure 1C), a typical structural feature of previously characterized fungal and plant hexose transporters [8],[19]. Sequence comparisons revealed a moderate similarity (less than 30% identity) of Srt1 to a large group of transport proteins (Figure S3) that includes numerous well-characterized high-affinity monosaccharide transporters from plants and fungi as well as some low-affinity maltose transporters from Saccharomyces cerevisiae [20][22], Pichia angusta (synonym: Hansenula polymorpha [23]), or Schizosaccharomyces pombe [24]. Phylogenetic analyses revealed that Srt1 is most closely related to a small group of so-far uncharacterized proteins (Figure S3).…”
Section: Resultsmentioning
confidence: 84%
“…Thus, the affinity of Srt1 for sucrose is several 100-fold to several 1,000-fold higher than that of the fungal maltose/maltotriose transporters [24],[28]. Moreover, its affinity is also much higher than that of higher plant sucrose transporters (20-fold to more than 200-fold), which catalyze sucrose uptake with K M values in the millimolar range [23].…”
Section: Resultsmentioning
confidence: 95%
“…In our previous work, we have described the MAL gene cluster that is responsible for the utilization of maltose and sucrose in Hansenula polymorpha [1,2]. Cloning of the maltase gene (HpMAL1) of the above mentioned cluster showed that the promoter (P MAL1 ) of this gene was also functional in Escherichia coli, as high maltase activity in HpMAL1-possessing transformants was observed [3].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to Saccharomyces yeasts, there are some reports that describe a cluster of three genes encoding a maltose permease, an a-glucosidase (maltase), and a transcription factor in Hansenula polymorpha (Viigand et al, 2005;Viigand and Alamäe, 2007), or a clustering of maltase and maltose permease genes in Torulaspora delbrueckii (Alves-Araújo et al, 2004) and Kluyveromyces lactis (Fairhead and Dujon, 2006). Thus far, however, there are no reports concerning such a cluster in filamentous fungi, and hence this is the first report that characterizes the functional maltose-utilization cluster in filamentous fungi.…”
Section: Discussionmentioning
confidence: 99%
“…B, BamHI; H, HindIII; K, KpnI; P, PstI; S, SalI; Sc, ScaI; and X, XhoI. For comparison, the organization of the MAL clusters from yeasts S. cerevisiae (retrieved from the Saccharomyces genome database (http://www.yeastgenome.org/)) and H. polymorpha (P. angusta)(Viigand et al, 2005) is also shown with that of the MAL homolog cluster present in A. oryzae genome. In the MAL cluster of H. polymorpha, HPMAL1, HPMAL2, and HPMAL3 code for maltase, maltose permease, and putative MAL activator, respectively.…”
mentioning
confidence: 99%